Concentrations, source apportionment and potential health risk of toxic metals in foodstuffs of Bangladesh. (2nd October 2021) - Kormoker, Tapos; Proshad, Ram; Islam, Md. Saiful; Shamsuzzoha, Md.; Akter, Ayesha; Tusher, Tanmoy Roy
Abstract: Toxic metal contamination in foodstuff is a major concern for public health and human beings are continuously exposed to toxic metals through consumption of cereals, pulses, vegetables, fruits, and other crops grown in the metals contaminated soil. The present study was conducted to investigate the concentrations of chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), cadmium (Cd), and lead (Pb) in foodstuffs and their possible human health risks in Jhenaidah and Kushtia districts, Bangladesh. The range of Cr, Ni, Cu, As, Cd, and Pb in the studied foodstuffs were 1.57–12.52, 1.71–37.78, 1.97–16.67, 0.36–3.72, 0.00–4.02, and 1.04–10.88 mg/kg dw, respectively. Multivariate principal component analysis revealed significant anthropogenic contributions of Cr, Cu, As, and Pb in the studied foodstuffs. The estimated daily intake (EDI) values of all the metals except Cu were higher than the maximum tolerable daily intake (MTDI). The target hazard quotients (THQs) of the studied metals, excluding Cr, from all foodstuffs were higher than 1, indicating that if people consume these types of foods in their diet, they might pose risk to these metals. The estimated target carcinogenic risk of As was higher than USEPA standard (10 −4 ), indicating increased risk of cancer for adults and children in the study area.